2022
DOI: 10.1017/jfm.2022.268
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws for drag-to-thrust transition and propulsive performance in pitching flexible plates

Abstract: The propulsion of a pitching flexible plate in a uniform flow is investigated numerically. The effects of bending stiffness ( $K$ ), pitching amplitude ( $A_L$ ) and frequency ( $St$ ) on the wake patterns, thrust generations and propulsive performances of the fluid–plate system are analysed. Four typical wake patterns, i.e. von Kármán, reversed von Kármán, deflected and chaotic wakes, emerge from various kinematics, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…When driving at resonance condition, our model fails to give the accurate response parameter as that from simulation provided by Peng et al (2022). This is because the driving pitching amplitude used by Peng et al is 0.1, which makes the finalized pitching amplitude obviously larger than the ones that the linear inviscid theory holds.…”
Section: Model Validationmentioning
confidence: 72%
“…When driving at resonance condition, our model fails to give the accurate response parameter as that from simulation provided by Peng et al (2022). This is because the driving pitching amplitude used by Peng et al is 0.1, which makes the finalized pitching amplitude obviously larger than the ones that the linear inviscid theory holds.…”
Section: Model Validationmentioning
confidence: 72%
“…Peng et al. (2022) have shown that, for a passive pitching foil, while the trailing-edge kinematics is a valid representative for the propulsion performance (e.g. power coefficient), using the entire motion of the foil slightly better represents the propulsion performance.…”
Section: Resultsmentioning
confidence: 99%
“…The resonance theory proposes that fish adjust the structural stiffness to match the resonance frequency of the system with the beating frequency, thereby reducing energy consumption (Blight 1977). The theory is supported by several experimental and computational studies, which found that the local thrust peaks of a plunging plate coincide with its trailing-edge amplitude peaks in the beating frequency spectrum and the efficiency peaks also largely correspond to the thrust peaks (Quinn, Lauder & Smits 2014;Floryan & Rowley 2018;Hoover et al 2018;Peng et al 2022). Some other studies which support the hydrodynamics mechanism, however, did not observe the match of the frequencies.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations